Translational control of epidermal growth factor receptor in neurodegenerative diseases - Smalley, Daniel. S. (2017)
Epidermal growth factor receptor (EGFR) is a key modulator of a number of cellular processes such as cell fate, proliferation, migration, and apoptosis. The EGFR gene is commonly amplified in a number of cancers and EGFR has been implicated in Alzheimer’s disease, but its role in this context is uncertain. An internal ribosome entry site (IRES) within the EGFR 5’untranslated region (UTR) has been previously discovered which maintains EGFR expression under hypoxic conditions and has a high requirement for the eukaryotic initiation factor (eIF) 4A helicase. Requirement for eIF4A suggests that the structure of the IRES is important in its regulation. Identifying the structure of the IRES and the conditions in which the IRES is active could lead to the development of therapeutics targeting the IRES.